Method for preparing biochar from shaddock peel and application of biochar

The method of preparing biochar through grapefruit peel has solved the problems of complex process, low yield and poor adsorption effect in the prior art, and achieved efficient and simple preparation of biochar and efficient heavy metal adsorption effect.

CN119750573AInactive Publication Date: 2025-04-04GUANGXI TEACHERS EDUCATION UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411914511.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing biochar preparation methods are complex in technology, difficult to control the synthesis parameters, low biochar yield and poor adsorption effect, which cannot meet the quality and performance requirements of high-end products.

Method used

Using grapefruit peel as raw material, it is dried, crushed, mixed with the activator Na2CO3 and then carbonized in a muffle furnace to prepare biochar with good yield and adsorption effect.

Benefits of technology

It has achieved simplification of the biochar preparation process, easy control of synthesis parameters, improved biochar yield and improved adsorption effect, and is suitable for efficient adsorption of heavy metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750573A_ABST
    Figure CN119750573A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing biochar from shaddock peel. The method comprises the following operation steps: (1) cutting the shaddock peel into pieces, putting the shaddock peel pieces into a drying oven, completely drying the shaddock peel pieces, and taking out the dried shaddock peel pieces for later use; (2) putting the completely dried shaddock peel into a crusher for crushing, and sieving with a 100-mesh sieve to obtain shaddock peel powder; (3) mixing the shaddock peel powder with an activating agent according to a weight ratio of (2-5): 1, and carbonizing in a muffle furnace to obtain shaddock peel charcoal; and (4) naturally cooling the shaddock peel biochar, cleaning with nitric acid until no bubble is generated, carrying out suction filtration, washing with deionized water until the solution is neutral, drying the shaddock peel biochar in a drying oven, sieving with a 100-mesh sieve, and putting the shaddock peel biochar in a sealed bag to prepare the biochar. The method is simple in preparation process, raw materials are easy to obtain, synthesis parameters are easy to control, the biochar yield is high, the biochar is used for adsorbing heavy metal, the adsorption effect is good, and the removal rate is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing biochar, and specifically to a method for preparing biochar from grapefruit peel and application thereof. Technical Background

[0002] Biochar is a material made from biomass, which is carefully fired through a high-temperature carbonization process. The particularity of its internal structure comes from the breaking of the original chemical bonds and the birth of new combinations in the furnace of pyrolysis and carbonization of biomass raw materials, which builds a unique "skeleton" interwoven with aromatic compounds and minerals. The elemental composition of biochar is rich and colorful, mainly including carbon (C), hydrogen (H), oxygen (O), nitrogen (N), sulfur (S), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), silicon (Si), etc. Among them, carbon is the most abundant, followed by hydrogen and oxygen, while mineral elements are mainly precipitated in the ash, adding more functionality and diversity to biochar. The characteristics of biochar cover two dimensions: physical properties and chemical properties. In the field of physical properties, biochar has demonstrated its importance in materials science with its key indicators such as pore size, specific surface area, particle size and mechanical strength. Its significant specific surface area and rich pore structure, coupled with the diversity of surface functional groups, give biochar unique adsorption and catalytic potential, and also have a profound impact on its reaction kinetics. These characteristics, as key parameters for evaluating the quality of biochar, are of decisive significance for its application in environmental governance, energy conversion and other fields. The chemical properties of biochar, including its elemental composition, pH value and the richness of surface functional groups, largely shape its performance in practical applications.

[0003] At present, the preparation methods of biochar generally include hydrothermal carbonization, gasification, rapid carbonization and baking carbonization. The gasification method uses gasifying agents such as air, oxygen and water vapor to oxidize the raw materials. Gasification requires high temperature (usually above 700°C) and a small amount of oxygen or steam. Solid, liquid and gas products will also be formed during the gasification process. The biochar yield of the gasification method is low. The hydrothermal carbonization method is to place the raw materials in a reaction vessel, add water and mix them, and then increase the temperature and pressure. Hydrothermal carbonization is usually carried out at 200-374°C. The operation of the hydrothermal carbonization method is complicated and it is difficult to control the synthesis parameters. Rapid carbonization refers to the reaction of the raw materials at 1-2MPa and 300-600°C for 30 minutes, and the resulting products are mainly gaseous and solid. Baking carbonization is to remove moisture and oxygen from the raw materials under oxygen-limited and low temperature (usually 200-300°C) conditions and convert them into hydrophobic solid products. Due to the short carbonization time of the rapid carbonization method and the baking carbonization method, some raw materials are not oxidized during the preparation process, resulting in low biochar yield. In addition, its pore structure is relatively large, the specific surface area is small, and the adsorption capacity is poor.

[0004] Therefore, the biochar obtained by the existing preparation methods cannot meet the quality and performance requirements of downstream high-end products. It is urgent to develop a biochar preparation method with simple preparation process, easy-to-control synthesis parameters, high biochar yield and good adsorption effect for application in the adsorption of heavy metals. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing biochar from grapefruit peel and its application. The method has a simple preparation process, readily available raw materials, easy-to-control synthesis parameters, high biochar yield and good adsorption effect. The biochar is applied to heavy metal adsorption with good removal effect.

[0006] The present invention solves the above technical problems with the following technical solutions:

[0007] The present invention provides a method for preparing biochar from grapefruit peel, comprising the following steps:

[0008] (1) Cut the grapefruit peel into pieces and put them into an oven to dry completely before taking them out for later use;

[0009] (2) putting the completely dried grapefruit peels in step (1) into a grinder and crushing them, and passing them through a 100-mesh sieve to obtain grapefruit peel powder for later use;

[0010] (3) mixing the grapefruit peel powder of step (2) with an activator in a weight ratio of 2-5:1 and placing the mixture in a muffle furnace for carbonization treatment to obtain grapefruit peel biochar;

[0011] (4) After the grapefruit peel biochar is naturally cooled, it is washed with 1 mol / L nitric acid until no bubbles are generated, then filtered, and then washed with deionized water until neutral. The grapefruit peel biochar is then placed in a drying oven for drying, and finally screened with a 100-mesh standard sieve. The grapefruit peel biochar is then placed in a sealed bag to prepare the biochar.

[0012] In step (1) of the present invention, the pomelo peel is cut into pieces with a length and a width not exceeding 1 cm.

[0013] In step (1) of the present invention, the temperature of the oven is set to 75° C. and the drying time is set to 12 hours.

[0014] In step (3) of the present invention, the activating agent is Na2CO3.

[0015] In step (3) of the present invention, the temperature of the muffle furnace carbonization treatment is 400-700° C. and the time is 2-5 hours.

[0016] In step (4) of the present invention, the drying temperature of the drying oven is set to 75° C., and the grapefruit peel biochar is dried until completely dry.

[0017] Application of the biochar of the present invention: the prepared biochar is used for adsorbing heavy metals, and during operation, the biochar is added into a heavy metal-containing solution with a pH value of 3-8 for adsorption treatment.

[0018] The amount of the biochar used is 0.1 g of biochar per 100 mL of the heavy metal-containing solution.

[0019] The heavy metal-containing solution is a Zn ion-containing solution or a Pb ion-containing solution.

[0020] The method of the present invention has the following beneficial effects:

[0021] (1) The method of the present invention prepares biochar under oxygen-limited conditions, which overcomes the disadvantage that the products of the gasification preparation process are solid, liquid and gas, and increases the yield of biochar.

[0022] (2) The carbonization process of the method of the present invention uses a muffle furnace, which can determine the carbonization time and temperature. The preparation process is simple and has good repeatability, overcoming the shortcomings of the hydrothermal carbonization method, which is complicated to operate and difficult to control the synthesis parameters.

[0023] (3) The carbonization time of the method of the present invention is set to 2-5h, the raw materials are completely carbonized, and the biochar yield is high, which overcomes the shortcomings of the rapid carbonization method and the baking carbonization method due to the short carbonization time, part of the raw materials are not carbonized, resulting in low biochar yield.

[0024] (4) The method of the present invention uses grapefruit peel as a raw material, which is easy to obtain, and uses sodium carbonate as an activating agent, so that the prepared biochar has a small pore structure and a large specific surface area. The method of use is simple and the adsorption effect is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a graph showing the removal rate (a) and adsorption amount (b) of heavy metal Zn by the biochar of Examples 1-16 of the present invention.

[0026] Figure 2 It is a graph showing the removal rate (a) and adsorption amount (b) of heavy metal Pb ions by the biochar of Examples 1-16 of the present invention.

[0027] Figure 3 This is a graph showing the N2 absorption and desorption curves of the biochar of Example 10 of the present invention.

[0028] Figure 4 This is a pore size distribution diagram of the biochar of Example 10 of the present invention.

[0029] Figure 5 This is the SEM image of grapefruit peel powder.

[0030] Figure 6This is a SEM image of the biochar prepared in Example 10 of the present invention.

[0031] Figure 7 ] are infrared spectra of grapefruit peel powder (a) and biochar prepared in Example 10 (b).

[0032] Figure 8 This is a curve diagram of the optimal pH range of the solution containing heavy metal Zn treated with biochar prepared in Example 10 of the present invention.

[0033] Fig. 9 It is a curve diagram of the effect of the biochar prepared in Example 10 of the present invention on the removal rate (a) and adsorption amount (b) of Zn adsorbed by heavy metal Zn solutions with different pH values.

[0034] Fig.10 This is a curve chart showing the effect of the biochar prepared in Example 10 of the present invention on the adsorption of Zn ions in different adsorption time periods.

[0035] Fig.11 It is a QF (a) and QS (b) kinetic fitting curve diagram of Zn ions treated with biochar prepared in Example 10 of the present invention.

[0036] Fig.12 This is the adsorption isotherm model of Zn ions by the biochar prepared in Example 10 of the present invention.

[0037] Fig.13 This is a curve diagram of the optimal pH range of the solution containing heavy metal Pb treated with biochar prepared in Example 10 of the present invention.

[0038] Fig.14 This is a curve chart showing the effect of the biochar prepared in Example 10 of the present invention on the adsorption of Pb ions in heavy metal Pb solutions at different pH values.

[0039] Fig.15 This is a curve chart showing the effect of the biochar prepared in Example 10 of the present invention on the adsorption of Pb ions in different time periods.

[0040] Fig.16 These are the QF (a) and QS (b) kinetic models of the treatment of heavy metal Pb by the biochar prepared in Example 10 of the present invention.

[0041] Fig.17 This is a curve diagram showing the effect of the biochar prepared in Example 10 of the present invention on the adsorption of Pb ions at different initial ion concentrations.

[0042] Fig.18 This is the Lm (a) and Fd (b) isothermal adsorption model diagram of the heavy metal Pb by the biochar prepared in Example 10 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0044] The method for preparing biochar from grapefruit peel of the present invention has the following specific operating steps:

[0045] (1) Prepare grapefruit peels, cut the grapefruit peels into pieces with a length and width not exceeding 1 cm, and put them into an oven for drying. After they are completely dried, take them out for later use. The temperature of the oven is set to 75° C., and the drying time is set to 12 hours.

[0046] (2) After the grapefruit peel in step (1) is completely dried, it is taken out and put into a grinder for crushing. After passing through a 100-mesh sieve, the grapefruit peel powder is obtained for later use.

[0047] (3) The grapefruit peel powder of step (2) is mixed with the activator Na2CO3 in a weight ratio of 2-5:1, and then placed in a muffle furnace for calcination at 400-700°C for 2-5 hours to obtain grapefruit peel biochar.

[0048] (4) After the grapefruit peel biochar of step (3) is naturally cooled, it is placed in a beaker and washed with 1 mol / L nitric acid until no bubbles are generated. Then, it is filtered and washed with deionized water until it is neutral. Then, the biochar is placed in a drying oven at 75° C. and dried until it is completely dry. Finally, it is screened through a 100-mesh standard sieve and the biochar is placed in a sealed bag for storage, thereby preparing the biochar.

[0049] The preparation processes of Examples 1-16 of the present invention are carried out according to the above specific operation steps, with the only difference being the parameters of the grapefruit peel powder and activator dosage ratio, firing temperature and time used in step (3). The specific parameters are shown in Table 1.

[0050] Table 1 Process parameters of step (3) in the preparation process of Examples 1-16

[0051]

[0052]

[0053] The following are the performance tests and application experiments of the product of the present invention:

[0054] Weigh 0.1g of the prepared biochar and add it to a 100mL Zn ion solution with a concentration of 100mg / L for adsorption experiment. The solution before and after adsorption was tested using an atomic absorption spectrophotometer to calculate the removal rate and adsorption amount of Zn ions by biochar under different conditions. The calculation method of removal rate and adsorption amount is as follows:

[0055] When sampling, use a pipette to carefully measure 1 mL of the clear upper liquid for both the original solution and the solution after adsorption treatment. In view of the limited measurement range of the atomic absorption spectrometer, the extracted Zn solution needs to be appropriately diluted. Specifically, the Zn solution needs to be diluted 100 times to meet the concentration range required for the test. During the detection process, the preparation of the standard curve is crucial to ensure the accuracy of the experimental results. To this end, the experiment uses a 1000 mg / L standard solution to ensure the accuracy and reliability of the standard curve. In order to ensure that the ion concentration in the standard curve is within the test range of the atomic absorption spectrophotometer, the Zn concentration gradient is set to 0.1, 0.2, 0.3, 0.5, 0.7, 0.8, 0.9, 1, 1.2 mg / L.

[0056] By using atomic absorption spectrophotometry, the absorbance values ​​corresponding to each concentration in the standard curve were measured, and a standard curve for Zn ions was drawn based on this. The absorbance of the biochar in the solution before and after adsorption was measured, and then the concentration of the solution before and after adsorption was calculated based on the previously drawn standard curve. The adsorption capacity of biochar for Zn was calculated based on formula 1, and the standard curve was used to calculate the adsorption capacity of biochar for Zn.

[0057] The removal rate of Zn by biochar is calculated by formula 2:

[0058]

[0059] In the formula, the adsorption amount of biochar Q e (unit: mg / g), the removal rate w can be calculated by the following parameters: the ion concentration c1 in the solution before adsorption (unit: mg / L), the ion concentration c2 in the solution after adsorption (unit: mg / L), and the mass M of the added biochar c (unit: g), the total volume V of the adsorption solution in the conical flask (unit: L).

[0060] The results of the removal rate (a) and adsorption amount (b) of heavy metal Zn by the biochar of Examples 1-16 of the present invention are shown in Figure 1 As shown in Figure 2, the removal rate (a) and adsorption amount (b) of heavy metal Pb ions are shown in Figure 2. Figure 2 shown.

[0061] The removal rates of heavy metal Zn by the biochars of Examples 1-16 were 38.23%, 46.44%, 48.81%, 50.82%, 50.64%, 51.19%, 52.28%, 50.82%, 51%, 55.01%, 51.92%, 48.08%, 46.99%, 48.27%, 51.19%, and 47.72%, respectively; the adsorption amounts were 38.23 mg / g , 46.44mg / g, 48.81mg / g, 50.82mg / g, 50.64mg / g, 51.19mg / g, 52.28mg / g, 50.82mg / g, 51m g / g, 55.01mg / g, 51.92mg / g, 48.08mg / g, 46.99mg / g, 48.27mg / g, 51.19mg / g, 47.72mg / g.

[0062] The removal rates of heavy metal Pb by the biochar of Examples 1-16 are 40.38%, 36.17%, 29.23%, 33.15%, 72.33%, 38.58%, 57.87%, 41.89%, 62.38%, 79.26%, 67.51%, 67.21%, 65.10%, 59.07%, 59.67% and 63.59% respectively; the adsorption amounts are 516 mg / g, 462 mg / g, 373 mg / g, 423 mg / g, 923 mg / g, 493 mg / g, 739 mg / g, 535 mg / g, 796 mg / g, 1012 mg / g, 862 mg / g, 858 mg / g, 831 mg / g, 754 mg / g, 762 mg / g and 812 mg / g respectively.

[0063] according to Figure 1 and Figure 2 The experimental results show that the biochar of Example 10 (i.e., the biochar prepared at a firing temperature of 600°C, a firing time of 3h, and a ratio of grapefruit peel powder to activator Na2CO3 of 5:1) has a higher adsorption capacity (55.01mg / g) and removal rate (55.01%) for heavy metal Zn, and a higher adsorption capacity (1012mg / g) and removal rate (79.62%) for heavy metal Pb than the biochar prepared under other conditions, indicating that the optimal preparation conditions are a firing temperature of 600°C, a firing time of 3h, and a ratio of grapefruit peel powder to activator of 5:1.

[0064] Characterization of the biochar of the present invention

[0065] The biochar obtained in Example 10 of the present invention was characterized by specific surface area (BET), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FT-IR). Figure 3As shown in the figure, it is an intuitive display of the N2 adsorption-desorption curve obtained after the test data is processed. The pore size of the biochar is analyzed, and the pore size distribution is shown in Figure 4 As shown in the figure, the average pore size of biochar is 3.88 nm and the specific surface area is 874.15 m 2 / g, total pore volume is 0.5835cm 3 / g.

[0066] Figure 5 and Figure 6 SEM images of grapefruit peel powder and biochar prepared in Example 10 are shown respectively. Compared with grapefruit peel powder, the surface of the prepared biochar has a porous structure, is irregular in shape, has many surface defects, and has a relatively uniform pore size distribution. It is rough and porous, which is conducive to increasing the total specific surface area of ​​activated carbon and provides abundant adsorption sites. The outer edge of the pore opening is thin and uneven, which may be related to the activation pore formation of the sodium carbonate activator. Its abundant pore structure is caused by the dissolution and activation reaction caused by the reduction of the sodium element in the sodium carbonate. It can be seen that it has considerable adsorption and removal effects on heavy metals.

[0067] The Fourier transform infrared spectra of grapefruit peel powder and biochar prepared in Example 10 are as follows: Figure 7 As shown, Figure 7 (a) is grapefruit peel powder, Figure 7 (b) is the biochar prepared in Example 10. Figure 7 (a) Fourier transform infrared spectrum, we can observe 618, 1032, 1417, 1631, 2923, 3445cm -1 Infrared characteristic vibration peaks appear at the positions of -1 The characteristic peaks at 1417 and 1034 cm -1 The characteristic peaks near 1613 cm-1 can be attributed to the stretching vibration of CO or the skeleton vibration of the CC single bond in biochar. -1 The characteristic peaks are caused by the stretching vibration of the C=C double bond in biochar. -1 The presence of the characteristic peaks seems to be due to the presence of OH, which suggests that the biochar contains a certain amount of carboxyl groups. Figure 7 (b) Fourier transform infrared spectrum, it can be observed that the wavelengths of the infrared spectrum are about 820, 1060, 1380, 1630, 2930, and 3440 cm -1 Infrared characteristic vibration peaks appeared at the positions of 3440, 2930, and 2340 cm -1The presence of the characteristic peak seems to be due to the presence of OH, which suggests that the biochar contains a certain amount of carboxyl groups. -1 The characteristic peaks of 1380 and 1060 cm are caused by the stretching vibration of the C=C double bond in biochar. -1 The characteristic peaks near 820 cm-1 can be attributed to the stretching vibration of CO or the skeleton vibration of the CC single bond in biochar. -1 The characteristic peak at , which seems to be related to the presence of CH, has a certain relationship with the presence of olefin groups in biochar. The infrared spectrum shows that biochar has been successfully prepared.

[0068] The adsorption performance test of biochar of the present invention on Zn ions is as follows:

[0069] (1) Determination of pH value of heavy metal solution

[0070] 0.100g of biochar was added to each conical flask containing 100mL of 100mg / L Zn ion solution, and the initial pH value of the ion solution was precisely controlled with the help of 0.1mol / L NaOH and 0.1mol / L HNO3. According to HYDRAQL software and chemical stability constants, the forms of Zn ions at different pH values ​​in water environments are as follows: Figure 8 As shown in the figure, according to the simulation results, the pH value range for Zn ions is 4.0 to 8.0. 10 mL of supernatant was accurately taken out with a pipette and detected by atomic absorption spectrometry. The adsorption of Zn by biochar under different pH conditions was calculated. The results are shown in Fig. 9 As shown in the figure, the adsorption capacity curve and removal rate curve of biochar for Zn both show an upward trend with the increase of pH value. When the pH is 8.0, biochar has a strong adsorption capacity for heavy metal Zn and a high removal rate.

[0071] (2) Effect of adsorption time

[0072] Under the optimal pH conditions, 0.100 g of biochar was placed in 500 mL conical flasks containing different concentrations of Zn ions. The specific ion concentrations were 100, 500, and 1000 mg / L, and the volume of the Zn solution was 500 mL. In order to explore the changes of the adsorption process over time in detail, samples were taken at specific time points of 1, 2, 5, 10, 15, 20, 30, 40, 60, and 90 min. The adsorption behavior and dynamic changes of biochar in solutions of heavy metal ions with different concentrations can be understood more accurately. Considering time, the biochar adsorption data obtained are not only suitable for the fitting analysis of the first-order kinetic model (QS) and the second-order kinetic model (QF), but also can be used to study the adsorption process of biochar in more depth.

[0073] like Fig.10 As shown in the figure, the amount of Zn adsorbed by biochar in the solution shows an upward trend over time, that is, the longer the adsorption time, the greater the amount of Zn adsorbed by biochar. Although the amount of Zn adsorbed by biochar increases with time, its adsorption rate of Zn gradually slows down and tends to balance overall. It is particularly noteworthy that the slope of the adsorption curve of biochar shows a significant increase trend in the first 40 minutes of Zn ion adsorption. As time goes by, due to the numerous functional groups on the surface of biochar and the rich pore structure, and the relatively high concentration of Zn ions in the solution, biochar shows a faster adsorption rate in the initial adsorption stage. However, as time goes by, the adsorption curve of biochar gradually tends to be stable, which is due to the gradual saturation of adsorption sites, resulting in a decrease in adsorption efficiency. At the same time, the Zn concentration in the solution is also gradually decreasing, resulting in an increasing difficulty in the combination between the two. More importantly, when metal ions successfully enter the pores of biochar or combine with functional groups, they will block the channels for subsequent ion exchange. This directly leads to a phenomenon that although the adsorption amount is still increasing, the adsorption rate is gradually slowing down, the curve gradually flattens, and finally the biochar reaches a state of dynamic adsorption equilibrium.

[0074] Adsorption kinetics model analysis

[0075] When analyzing the adsorption process of biochar on metal ions Zn, its adsorption mechanism may involve physical adsorption or chemical adsorption. Through in-depth research and fitting of the data of biochar adsorption of Zn under different time conditions, it can be further determined whether its adsorption process is more consistent with the QF kinetic model or the QS kinetic model, or whether the two are not completely consistent. The following are the formulas corresponding to the two models:

[0076] The specific expression of the formula of the QF kinetic model is as follows:

[0077]

[0078] or

[0079] ln(q e -q t )=ln(q e )+(-k1)t (4)

[0080] The specific expression of the formula of the QS kinetic model is as follows:

[0081]

[0082] or

[0083]

[0084] In the above expression, the adsorption amount of Zn at a specific time is expressed as q t , in mg / g. For saturated adsorption, use q e The unit is mg / g. The sampling time is t, which is expressed in minutes (min). In the QF kinetic model, the rate constant is named k1, which is expressed in min. -1 The rate constant in the QF kinetic model is called k2, and its unit is g·min / mg.

[0085] By using formula (4) and formula (6) to conduct in-depth fitting analysis on the adsorption time data of Zn by biochar, the corresponding simulation curve was successfully drawn, which is specifically shown in Fig.11 After calculation, the relevant parameters of the model were obtained. Please see Table 2 for detailed data information.

[0086] Table 2 Kinetic fitting parameters of Zn ion adsorption on biochar

[0087]

[0088]

[0089] According to the kinetic fitting parameter information of Zn listed in Table 2, under different conditions of Zn solution concentration of 100, 500, and 1000 mg / L, the parameter fitting correlation coefficient R of biochar for QS kinetic model 2 It is generally higher than the QF kinetic model, indicating that the process of biochar adsorption of Zn is more consistent with the description of the QS kinetic model, which may mean that in addition to the site adsorption mechanism, there are also processes such as ion exchange and complexation when biochar adsorbs Zn. Therefore, it can be inferred that the adsorption process of biochar on Zn is mainly a reaction process dominated by chemical adsorption.

[0090] Effect of initial concentration of heavy metal solution

[0091] Based on the optimal pH value and adsorption equilibrium time, Zn solutions with different ion concentrations were prepared, and the concentrations were 50, 100, 150, 200, 250, 400, 600, 800, 1000, 1500, and 2000 mg / L, respectively. 0.100 g of biochar was placed in a conical flask, and 100 mL of Zn solution of each initial concentration was added. In order to further explore the adsorption characteristics of biochar for Zn, the adsorption data fitting method was adopted, and the data were deeply compared and analyzed with the Langmuir and Freundlich adsorption isotherm models.

[0092] The Langmuir adsorption isotherm model and the Freundlich adsorption isotherm model were used to fit the data of Zn adsorption by biochar under different concentration conditions. By comparing the fitting results, it can be clearly determined whether the adsorption process belongs to the single-layer adsorption or multi-layer adsorption type.

[0093] The specific expression of the formula of the Langmuir adsorption isotherm model is as follows:

[0094]

[0095] In the above formula, c e It refers to the concentration of ions in the solution after the adsorption process is completed, and its unit of measurement is mg / L. m represents the maximum adsorption capacity that biochar can achieve, and its unit of measurement is mg / L. m It is a key constant in the Langmuir adsorption isotherm model, K m The higher the value, the better the adsorption performance of the adsorbent.

[0096] The Freundlich adsorption isotherm model, as an empirical adsorption isotherm model, shows a wider applicability than the Langmuir adsorption isotherm model. The main feature of this model is that the adsorption process presents an ordered hierarchical structure, in which the order of adsorption mainly depends on the strength of the binding ability between the adsorption sites on the adsorbent surface and the adsorbed substances. Specifically, those adsorption sites with stronger binding ability will preferentially participate in the adsorption process until they gradually approach saturation, and then those adsorption sites with relatively weaker binding ability will begin to participate in the adsorption process.

[0097] The specific expression of the formula of the Freundlich adsorption isotherm model is as follows:

[0098]

[0099] In the above formula, C e It indicates the concentration of ions in the solution after adsorption is completed, and its unit of measurement is mg / L. e It refers to the adsorption amount measured in the experiment, and its unit of measurement is mg / L. F As a core constant in the Freundlich adsorption isotherm model, it plays a key role in describing the adsorption process. In the data fitting process, 1 / n is an empirical parameter that can effectively reflect the intensity of the adsorption process and is thus used to evaluate the difficulty of the adsorption reaction of Zn by biochar. According to general knowledge, if the adsorption process is relatively easy, the value of 1 / n should be in the range of 0.1 to 0.5.

[0100] The adsorption data of Zn at different concentrations were calculated and the Langmuir and Freundlich adsorption isotherm models were used for detailed fitting analysis. The results are shown in Fig.12 middle, Fig.12 (a) and (b) represent the Lm (a) and Fd (b) isothermal adsorption models, respectively. In the fitting process, the two key values ​​of intercept and slope are obtained and substituted into formula (7) and formula (9), respectively. The parameter data of the two models are obtained by calculation. The specific values ​​are shown in Table 3 below.

[0101] Table 3 Adsorption isotherm model parameters

[0102]

[0103] It can be observed from Table 3 that the fitting correlation coefficient of biochar under the Langmuir adsorption isotherm model is superior to that of the Freundlich adsorption isotherm model for the adsorption parameter data of Zn. This finding reveals that the adsorption process of biochar on Zn mainly tends to be monolayer adsorption, and the adsorption amount reaches 136.61 mg / g. K in the formula F The value represents the affinity strength between the adsorbent and the adsorbate. The affinity strength between biochar and Zn ions is 26.798.

[0104] Adsorption experiment of Pb ions by the biochar obtained by the method of the present invention (Example 10):

[0105] (1) Effect of pH value of heavy metal solution

[0106] According to HYDRAQL software and chemical stability constants, the forms of Pb ions in different pH values ​​in water environments are as follows Fig.13 As shown, according to the simulation results, the pH value range is 3.0 to 6.0. Fig.14 The adsorption capacity of biochar is positively correlated with pH. The higher the pH, the greater the adsorption capacity. The adsorption capacity reaches the maximum when pH = 6, that is, the optimal pH value is 6.

[0107] (2) Effect of adsorption time on Pb adsorption amount

[0108] Depend on Fig.15 Analysis shows that the adsorption amount increases with the increase of adsorption time. In the first 100 minutes, the adsorption amount of Pb by biochar increases as time goes by. The adsorption process is a process in which the growth rate increases first, then decreases, and finally becomes flat. Although biochar does not reach the saturated adsorption amount after 100 minutes, the growth trend of the curve becomes very slow. Finally, the curve becomes flatter and flatter until it reaches the saturation point.

[0109] The QF (a) and QS (b) kinetic models of heavy metal Pb are shown in Fig.16 As shown, after Pb ion dynamics fitting, the calculated parameters are shown in Table 4.

[0110] Table 4 Pb(Ⅱ) kinetic fitting parameters

[0111]

[0112]

[0113] according to Fig.16 From the kinetic fitting parameters of Pb in Table 4, we can see that the QS fitting correlation coefficient of biochar is R 2 The parameters of the QF kinetic model are better, and the QS kinetic model can be selected. When biochar adsorbs Pb, in addition to the site adsorption mechanism, there are also processes such as ion exchange and complexation. Therefore, it can be inferred that the adsorption process of biochar on Pb is mainly a reaction process dominated by chemical adsorption.

[0114] (3) Effect of initial concentration on Pb adsorption

[0115] After Fig.17 From the analysis, it can be observed that there is a positive correlation between the amount of Pb adsorbed by biochar and the initial ion concentration. In particular, when the initial concentration is lower than 1000 mg / L, the slope of the adsorption curve is particularly significant. However, when the initial concentration exceeds 1000 mg / L, after a period of adsorption, the adsorption curve gradually becomes smooth.

[0116] The Langmuir model and Freundlich adsorption equilibrium model were used to fit the data of the adsorption amount of Pb under the influence of concentration, and the results were obtained. Fig.18 (a) and (b), and then the intercept and slope obtained during fitting are respectively substituted into formula (7) and formula (9) to calculate the parameter data of the two models, as shown in Table 5:

[0117] Table 5 Pb(Ⅱ) adsorption isotherm model parameters

[0118]

[0119] It can be observed from Table 5 that the fitting correlation coefficient of biochar under the Langmuir adsorption isotherm model is superior to that of the Freundlich adsorption isotherm model for the adsorption parameter data of Pb. This finding reveals that the adsorption process of biochar on Pb mainly tends to be monolayer adsorption, and the adsorption amount reaches 1409.79 mg / g. K in the formula FValue, which represents the affinity strength between the adsorbent and the adsorbate, the affinity strength between biochar and Pb ions is 1.03347.

Claims

1. A method for preparing biochar from grapefruit peel, characterized in that: The method comprises the following steps: (1) Cut the grapefruit peel into pieces and put them into an oven to dry completely before taking them out for later use; (2) putting the completely dried grapefruit peels in step (1) into a grinder and crushing them, and passing them through a 100-mesh sieve to obtain grapefruit peel powder for later use; (3) mixing the grapefruit peel powder of step (2) with an activator in a weight ratio of 2-5:1 and placing the mixture in a muffle furnace for carbonization treatment to obtain grapefruit peel biochar; (4) After the grapefruit peel biochar is naturally cooled, it is washed with 1 mol / L nitric acid until no bubbles are generated, then filtered, and then washed with deionized water until neutral. The grapefruit peel biochar is then placed in a drying oven for drying, and finally screened with a 100-mesh standard sieve. The grapefruit peel biochar is then placed in a sealed bag to prepare the biochar.

2. The method for preparing biochar from grapefruit peel according to claim 1, characterized in that: In the step (1), the pomelo peel is cut into pieces with a length and a width not exceeding 1 cm.

3. The method for preparing biochar from grapefruit peel according to claim 1, characterized in that: In the step (1), the temperature of the oven is set to 75° C. and the drying time is set to 12 hours.

4. The method for preparing biochar from grapefruit peel according to claim 1, characterized in that: In the step (3), the activating agent is Na2CO3.

5. The method for preparing biochar from grapefruit peel according to claim 1, characterized in that: In the step (3), the temperature of the muffle furnace carbonization treatment is 400-700° C. and the time is 2-5 hours.

6. The method for preparing biochar from grapefruit peel according to claim 1, characterized in that: In the step (4), the drying temperature of the drying oven is set to 75° C., and the grapefruit peel biochar is dried until completely dry.

7. The use of the biochar prepared by the method according to any one of claims 1 to 6, characterized in that: The prepared biochar is used to adsorb heavy metals. During the operation, the biochar is added into a heavy metal-containing solution with a pH value of 3-8 for adsorption treatment.

8. The use of biochar according to claim 7, characterized in that: The amount of the biochar used is 0.1 g of biochar per 100 mL of the heavy metal-containing solution.

9. The use of biochar according to claim 7, characterized in that: The heavy metal-containing solution is a Zn ion-containing solution or a Pb ion-containing solution.

Citation Information

Patent Citations

  • Preparation method of shaddock-peel-base activated carbon and application of shaddock-peel-base activated carbon to phenol-containing wastewater and waste gas

    CN105502384A

  • Composite photothermal conversion material based on shaddock peel as well as preparation and application of composite photothermal conversion material

    CN113247980A

  • Simple preparation method of carbon material with grapefruit flesh as raw material

    CN114477175A

  • Preparation method of N-S co-doped porous biochar and method for using N-S co-doped porous biochar as capacitor electrode

    CN116443876A

  • Integrated processes for pectin activation and mild extraction

    US20230272124A1